Criticisms toward the job creation bill and ethical reconstruction of legislators based on prophetic values - Ilham Dwi Rafiqi (Legality : Jurnal Ilmiah Hukum, 2021)
Post the issuance of Law Number 11 of 2020 concerning Job Creation, the public paid more attention by continuing to protest and criticize. This response occurred due to various legislative deviations noticed during the legislative process of the Job Creation Bill by not adhering to the principles and procedures for the formation of laws and regulations. The main cause for this deviation is due to the ethics of the legislators who are not thoroughly compliant and obedient toward the statutory regulations and social ethics. Legislators’ understanding of law and life tends to be influenced by materialistic-positivistic views that bring forth consumptive, hedonistic, and secular demeanors and behaviors. On this basis, this paper tries to criticize and reconstruct the legislators’ ethics in law-making. This study is using a normative juridical method and is supported by a philosophical approach. The outcomes of this research show that the process in the making of the Job Creation Bill tends to override the principle of transparency and public participation with a closed and hasty pattern so that it is a complete ulterior hasty agenda that prioritizes the concept of regulating and monitoring only (top-down). A work ethic based on prophetic values that are supported by the ground principles of a prophetic paradigm that includes humanization, liberation, and transcendence into a new form of construction to be able to create a better and just legislative process.